Paraffin Deposition and Methods of Deparafinination in the Transportation of Oils with Complex Rheological Properties - Seyfullayev , E.S. (Herald of Azerbaijan Engineering Academy, 2024)
A pressure drop in the oil flow, temperature difference, flow rate variation, roughness of the inner surface of the pipe and the degree of dispersibility of high molecular weight compounds are parameters that contribute to the deposit formation. The article studies the conditions under which the paraffin deposits are formed. As result, the existing methods for dealing with sediments both in the well and in subsequent transport processes have been studied. Along with the advantages of each method, the disadvantages are also provided. The methods of application of mechanical and heating of pipelines pump-compressor systems, as well as methods of applying protective coating, insulation, and reagents for prevention of sediment formation (deparaffinization) have been investigated.